Vatican Dicastery for Integral Human Development in service of migrants - NECEL, WOJCIECH (Prawo Kanoniczne, 2018)
Church history is also the history of a specific pastoral care for migrants. A great witness of concern for the people on road is the Apostolic Constitution "Exsul Familia" of Pius XII, which in essence, with its solutions, initiated the discussion on migrants during the Second Vatican Council and, consequently, forced many new indications and solutions described in details in conciliar and post-conciliar documents. While maintaining the right to religious freedom, each migrant poses a challenge to the Church to share with them the goods of the Church. A newcomer often requires an integral care and multifaceted support. A dicastery for. Integral Human Development, appointed on 08.17.2013. is tasked to indicate that migration is a structural phenomenon of the contemporary world. The migrants reflect all the problems of contemporary injustices, wars and hatred, shortcomings of medical services and non-compliance with fundamental human rights. Liquidation of the four Pontifical Councils taking up contemporary social problems and the appointment of the Dicastery is supposed to meet the problems people are facing today, regardless of their creed and religion, skin color, political view and language.